2021
DOI: 10.3389/fpsyt.2021.655087
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Delirium Are Different in the Very Old: A Comparative One-Year Prospective Cohort Study of 5,831 Patients

Abstract: Background: In an ever-aging society, health care systems will be confronted with an increasing number of patients over 80 years (“the very old”). Currently, knowledge about and recommendations for delirium management are often based on studies in patients aged 60 to 65 years. It is not clear whether these findings apply to patients ≥80 years.Aim: Comparison of younger and older patients with delirium, especially regarding risk factors.Methods: In this prospective cohort study, within 1-year, 5,831 patients (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A study using the DOSS in patients aged ≥18 found a positive score rate of 28% 37 . Two studies used the DOSS combined with the ICDSC and the ePA‐AC, and reported an overall positive score rate of 42% in patients aged ≥80 years, 36 and 12% in surgical patients and 27% in medical patients aged ≥18 years 38 . A study using either the DOSS (non‐ICU) or ICDSC (ICU) in patients aged ≥65 reported an overall positive score rate of 32% 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study using the DOSS in patients aged ≥18 found a positive score rate of 28% 37 . Two studies used the DOSS combined with the ICDSC and the ePA‐AC, and reported an overall positive score rate of 42% in patients aged ≥80 years, 36 and 12% in surgical patients and 27% in medical patients aged ≥18 years 38 . A study using either the DOSS (non‐ICU) or ICDSC (ICU) in patients aged ≥65 reported an overall positive score rate of 32% 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported on all inpatients aged ≥18 years, 12,[17][18][19]37,38 whereas one study only included the oldest old. 36 Some studies reported single assessments (prevalent delirium), and others repeated assessments during the inpatient stay (a combination of prevalent and incident delirium). Estimation of real-world sensitivity of the tools for delirium detection, reflecting concordance between positive score and true delirium occurrence rates, could only be done indirectly for all but one study.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…It is predicted that in the near future the estimated cost of care for delirium could exhaust the resources of health-care systems. 8,[21][22][23] Not incorporating delirium awareness programs could result in a lack of knowledge about this disease and complicate its clinical outcomes. 9 Helping older patients and caregivers understand the risk factors associated with this disease can also aid in its timely management.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, risk factors for delirium were evaluated in systematic reviews according to the type of patients. Risk of delirium is higher in very old patients [ 5 , 6 ]. Marquetand et al 2020 [ 6 ] in a recent work found that very old patients require only few precipitant factors to develop delirium.…”
Section: Introductionmentioning
confidence: 99%
“…Risk of delirium is higher in very old patients [ 5 , 6 ]. Marquetand et al 2020 [ 6 ] in a recent work found that very old patients require only few precipitant factors to develop delirium. Age was a risk factor also for patients after hip fracture surgery [ 7 ], vascular surgery [ 8 ], in knee and hip replacement patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%